Minat Pencarian Informasi Selama Pandemi Covid-19 Di Indonesia: Studi Google Trends - Adrina Esther Liaw; Fidia Paramitha Putri; Meiliza Ayu Qamarani; Nabilah Thifal Balma; Selly Tiyaningrum,; Sesa Magabe; Rizma Adlia Syakurah (Dian Nuswantoro Semarang, 2022)
Abstract The uncertainty of information on the development of the COVID-19 case in Indonesia has made the public have to independently search for COVID-19 information through various sources of information, such as the mass media and the internet. One of the tools that can be used to facilitate getting internet search data is Google Trends, an online portal that focuses on search trends or searches on Google pages within a certain period of time so that it monitors what keywords are mostly used by Indonesians in searching for data and information. regarding COVID-19 during this pandemic period .. The research method was carried out with the most keyword searches in Indonesia regarding COVID-19 during the pandemic period using Google Trends (https://trends.google.com/trends) from 1 January - 1 September 2020 The keywords chosen were the corona outbreak, corona disease, and the corona pandemic, which would be associated with each surge that occurred, analyzed and linked to the keyword search result data, namely